2009
DOI: 10.1542/peds.2008-1879
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fatigue Syndrome After Infectious Mononucleosis in Adolescents

Abstract: Background-Chronic fatigue syndrome (CFS) is a complex and controversial condition responsible for marked functional impairment. Infectious mononucleosis (IM) may be a predisposing factor for CFS. Among adults after IM, 9-12% may have symptomatic fatigue 6 months later. Rates of CFS in the general adolescent population are low (0.2%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
150
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 20 publications
4
150
0
5
Order By: Relevance
“…EBV is the most well-known virus to cause CFS/ME with rates of 13%, 7% and 4% at 6, 12 and 24 months after infection 27. The risk of developing CFS/ME after EBV is increased in adolescents who are female 27. The severity of infection is an important predictor of CFS/ME rather than a specific infection 28.…”
Section: Risk Factorsmentioning
confidence: 99%
“…EBV is the most well-known virus to cause CFS/ME with rates of 13%, 7% and 4% at 6, 12 and 24 months after infection 27. The risk of developing CFS/ME after EBV is increased in adolescents who are female 27. The severity of infection is an important predictor of CFS/ME rather than a specific infection 28.…”
Section: Risk Factorsmentioning
confidence: 99%
“…While the role of infectious agents in the development of CFS has not been proven [5,9,10], CFS is frequently reported in adolescents following Epstein-Barr virus (EBV) infection [2,11]. This relationship was further outlined by Katz et al [12] who demonstrated that the incidence of CFS after infectious mononucleosis persisted in 13%, 7% and 4% of children at 6, 12, and 24 months, respectively. Similarly, Marshall et al reported a 15% prevalence of EBV in pediatric CFS cases [13].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Sustained arousal might be caused by infections, 24 which seem to be precipitating factors in CFS. 25,26 However, the precise role of microorganisms in CFS remains unclear. Clonidine hydrochloride is a centrally acting agonist to the α 2 -adrenergic receptor.…”
mentioning
confidence: 99%